IDENTIFIKASI BUDAYA DI REGION ASIA TENGGARA - Apep Munawar (Jurnal Samudra Geografi, 2023)
Southeast Asia has land areas and islands with diverse physical characteristics. This condition affects the distribution of culture in Southeast Asia. A study with geohistorical approach was carried out to discover the origins of cultural development in Southeast Asia and the processes that influenced its development by taking into account the characteristics of each region which were influenced by geographical conditions and social conditions. This research uses a literature study approach. Data from relevant books and journals were collected and then analyzed to conclude. From the genealogical identification, it is known that the culture in the Southeast Asian region is rooted in the Malay culture, which is dominantly influenced by Chinese culture. Another dominant cultural feature is the life of the people who uphold the prevailing values and norms.